2012
DOI: 10.1136/fetalneonatal-2012-301809.259
|View full text |Cite
|
Sign up to set email alerts
|

Defining risks of instrumental delivery in a large UK cohort

Abstract: Background Instrumental delivery accounts for approximately 10-15% of UK deliveries. It is increasingly scrutinised for complication rates, yet there is variable data in the literature describing complication rates in the UK, with, for example, third degree tear rates for forceps deliveries of 8-12% being reported (RCOG 2010). This study sought to describe complication rates in a large UK cohort, which could subsequently be used to generate audit standards. Methods Data was collected from all instrumental de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Symptoms associated with pelvic floor trauma include pain, dyspareunia, and urinary and bowel incontinence. [94][95][96][97][98][99][100] However, a longitudinal prospective cohort study nested with a two-centre RCT of routine versus restrictive episiotomy for assisted vaginal birth reported that pelvic floor morbidities associated with assisted vaginal birth are often as prevalent, if not more prevalent, in the third trimester of pregnancy than postpartum. 101 This suggests that much of the pelvic floor morbidity reported by women in the weeks and months after an assisted vaginal birth may not be causally related to the procedure.…”
Section: Evidence Level 1++mentioning
confidence: 99%
See 1 more Smart Citation
“…Symptoms associated with pelvic floor trauma include pain, dyspareunia, and urinary and bowel incontinence. [94][95][96][97][98][99][100] However, a longitudinal prospective cohort study nested with a two-centre RCT of routine versus restrictive episiotomy for assisted vaginal birth reported that pelvic floor morbidities associated with assisted vaginal birth are often as prevalent, if not more prevalent, in the third trimester of pregnancy than postpartum. 101 This suggests that much of the pelvic floor morbidity reported by women in the weeks and months after an assisted vaginal birth may not be causally related to the procedure.…”
Section: Evidence Level 1++mentioning
confidence: 99%
“…Vacuum and forceps birth are associated with a higher incidence of episiotomy, pelvic floor tearing, levator ani avulsion and obstetric anal sphincter injury (OASI) than spontaneous vaginal birth. Symptoms associated with pelvic floor trauma include pain, dyspareunia, and urinary and bowel incontinence . However, a longitudinal prospective cohort study nested with a two‐centre RCT of routine versus restrictive episiotomy for assisted vaginal birth reported that pelvic floor morbidities associated with assisted vaginal birth are often as prevalent, if not more prevalent, in the third trimester of pregnancy than postpartum .…”
Section: Performing Assisted Vaginal Birthmentioning
confidence: 99%
“…ŞƂƇźƆƟƑƇƂƃ źƇźƅƟƁ ƋƌƊƍƄƌƍƊƂ ƈƋƇƈżƇƂƏ ƋƄƅź-žƈżƂƏ ƁźŽźƅƖƇƈŽƈ ƊƟżƇƙ ƊſƉƊƈžƍƄƌƂżƇƂƏ żƌƊźƌ ƍƉƊƈžƈżƀ ƉſƊƟƈžƍ žƈƋƅƟžƀſƇƇƙ ƁźƋżƟžƑƂż ƠƏ ƊƟƁ-ƇƈƋƉƊƙƆƈżźƇƍ ƇźƉƊźżƅſƇƟƋƌƖ. ũƈƁƂƌƂżƇƟ ƌſƇ-žſƇƐƟƠ ŻƍƅƂ ƁźŻſƁƉſƑſƇƟ Ƈź ƒƅƙƏƍ ƉƊſƇźƌźƅƖƇƈƠ ƋƄƅźžƈżƈƠ -żƂƆƍƒſƇƂƏ źŻƈƊƌƟż Ɓ 79,9% ƍ 2000 Ɗ. žƈ 74,7% ƍ 2021 Ɗ., ŜŲ Ɓ 95% Şő 0,93 (0,89-0,97), Ɗ<0,0001, ƌƟƅƖƄƂ Ɓź ƊźƏƍƇƈƄ żƂƉſƊſžƀźƘƑƈŽƈ ƁƇƂƀſƇƇƙ, ƆſžƂƑƇƂƏ ƅſŽźƅƖƇƂƏ źŻƈƊƌƟż ƍ ƌſƊƆƟƇƟ żƟž 12 žƈ 22 ƌƂƀƇƟż żźŽƟƌƇƈƋƌƟ Ɓ 27,9% žƈ 8,3%, ŜŲ Ɓ 95% Şő 0,23 (0,22-0,25), Ɗ<0,0001, ƉƊƂ ƈž-ƇƈƑźƋƇƈƆƍ ƁŻƟƅƖƒſƇƇƟ žƈƅƟ (ƋƉƈƇƌźƇƇƂƏ) źŻƈƊƌƟż ƟƁ 52,0% žƈ 67,4%, ŜŲ Ɓ 95% Şő 1,90 (1,98), Ɗ<0,0001. šź Ɛſƃ ƉſƊƟƈž ƍ ƋƌƊƍƄƌƍƊƟ ƊſƉƊƈžƍƄ-ƌƂżƇƂƏ żƌƊźƌ ƁŻƟƅƖƒƂƅźƋƙ žƈƅƙ ƎſƌƈƟƇƎźƇƌƂƅƖ-ƇƂƏ żƌƊźƌ Ɓ 20,0% žƈ 24,4%, ŜŲ Ɓ 95% Şő 1,24 (1,13-1,3), Ɗ<0,0001, Ɓź ƊźƏƍƇƈƄ ƁƇźƑƇƈŽƈ ƁŻƟƅƖ-ƒſƇƇƙ ƑźƋƌƈƌƂ ƇźƊƈžƀſƇƂƏ ƆſƊƌżƂƆƂ Ɓ 6,2% žƈ 11,6%, ŜŲ Ɓ 95% Şő 1,98 (1,86-2,1), Ɗ<0,0001, ƉƊƂ ƉƈƁƂƌƂżƇƟƃ ƌſƇžſƇƐƟƠ ƉƈƆſƊƅƂƏ žƟƌſƃ Ƈź ƉſƊƒƈƆƍ ƊƈƐƟ ƀƂƌƌƙ -13,8% Ɵ 12,8%, ŜŲ Ɓ 95% Şő 0,91 (0,86-0,96), Ɗ<0,0001 (ƌźŻƅ. 3) ŜƂƙżƅſƇƈ, Ɠƈ ƉƈƁƂƌƂżƇź žƂƇźƆƟƄź ƁźŽźƅƖ-ƇƂƏ ƊſƉƊƈžƍƄƌƂżƇƂƏ żƌƊźƌ żƟžŻƍƅźƋƙ Ɓź ƊźƏƍ-ƇƈƄ ƁƆſƇƒſƇƇƙ żƂƆƍƒſƇƂƏ ƋźƆƈżƟƅƖƇƂƏ (ƋƉƈƇ-ƌźƇƇƂƏ) Ɵ ƆſžƂƑƇƂƏ ƅſŽźƅƖƇƂƏ źŻƈƊƌƟż ƍ ƌſƊƆƟƇƟ żƟž 12 žƈ 22 ƌƂƀƇƟż żźŽƟƌƇƈƋƌƟ, ƄƟƅƖƄƟƋƌƖ ƙƄƂƏ ƁƆſƇƒƂƅźƋƙ Ɓ 68,8 Ƈź 1000 ƇźƊƈžƀſƇƂƏ ƀƂżƂƆƂ ƍ 2000 Ɗ. žƈ 43,2‰ ƍ 2021 Ɗ., ŜŲ Ɓ 95% Şő 0,63 (0,59-0,67), Ɗ<0,0001, ƌź ƉƈƆſƊƅƂƏ Ƈź ƉſƊƒƈ-Ɔƍ ƊƈƐƟ ƀƂƌƌƙ -Ɓ 11,9‰ žƈ 7,2‰ żƟžƉƈżƟžƇƈ, ŜŲ Ɓ 95% Şő 0,7 (0,66-0,74), Ɗ<0,0001.…”
Section: ǂƺƶʃƿʋƽǎƿʃ ƶ|ǃƽʃƶƹʒƿƿǒunclassified
“…Vacuum and forceps birth are associated with a higher incidence of episiotomy, pelvic ʶ oor tearing, levator ani avulsion and obstetric anal sphincter injury (OASI) than spontaneous vaginal birth. Symptoms associated with pelvic ʶ oor trauma include pain, dyspareunia, and urinary and bowel incontinence [94][95][96][97][98][99][100]. However, a longitudinal prospective cohort study nested with a two-centre RCT of routine versus restrictive episiotomy for assisted vaginal birth reported that pelvic ʶ oor morbidities associated with assisted vaginal birth are often as prevalent, if not more prevalent, in the third trimester of pregnancy than postpartum [101].…”
Section: Evidence Level 1+mentioning
confidence: 99%